2012
DOI: 10.1177/1474515112449539
|View full text |Cite
|
Sign up to set email alerts
|

Components of heart failure management in home care; a literature review

Abstract: There a several studies on HF care at home, testing interventions with a variety in number of components. Comparing the results to current standards, aspects such as collaboration between primary care and hospital care, titration of medication, and patient education can be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 96 publications
(222 reference statements)
1
31
0
2
Order By: Relevance
“…According to this the benefit of physical activity and exercise should be included in ECM. Interventions for CHF management in home care are described in a literature review of research (27). It was found that most studies reported multidisciplinary interventions including nurses, physicians, and other professionals, e.g.…”
Section: Discussionmentioning
confidence: 98%
“…According to this the benefit of physical activity and exercise should be included in ECM. Interventions for CHF management in home care are described in a literature review of research (27). It was found that most studies reported multidisciplinary interventions including nurses, physicians, and other professionals, e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Home monitoring can come in the form of telephone support and visits, the promotion of self-care and the use of a variety of external or implantable devices. Multi-component interventions variously incorporate enhanced team communication, care planning, education and support for patients and carers, direct access to hospital care and the use of information technologies (Jaarsma et al 2013 ). Tele medical monitoring service can combine with this support at home and reduce the number and duration of hospital admissions for worsening pathologies (Anker et al 2011 ), though may not currently be suitable for patients with cognitive, visual or other sensory impairments (van den Berg et al 2012 ).…”
Section: Detecting Deteriorationmentioning
confidence: 99%
“…Kompleksiteten ved hjertesvikt krever tverrfaglig oppfølging og koordinering, noe som tydeliggjøres i anbefalte retningslinjer for hjertesviktpasienter (40). Tidligere studier i andre land viser at mangel på samarbeid i oppfølgingen mellom tjenestenivåene er en kjent problemstilling (41). Det kom også tydelig frem i PasOpp-rapporten fra 2013, der pasienterfaringer ved norske sykehus ble undersøkt.…”
Section: Diskusjonunclassified